Recurrent expressions for reliability indicators of compound electropower systems - Sydor, A.R.; Teslyuk, V.M.; Denysyuk, P.Yu. (Технічна електродинаміка, 2014)
Main reliability indicators of unrestorable compound electropower systems are examined in this paper. A method of investigation of reliability indicators for compound electropower systems by means of generating functions is developed taking account of aging of the system’s output elements. Recurrent expressions are worked out for the failure probability in the prescribed availability condition, the failure frequency in the prescribed availability condition and the failure rate in the prescribed availability condition provided that the lifetime of ageing output elements is described by the Rayleigh distribution.